A unified model of transient poration induced by antimicrobial peptides - Amy Rice; Andriana C. Zourou; Myriam L. Cotten; Richard W. Pastor (Proceedings of the National Academy of Sciences, 2025)
Membrane active peptides (MAPs) represent a diverse group of agents that disrupt the integrity of lipid membranes. One class of MAPs, antimicrobial peptides (AMPs), destroy bacteria by transiently porating the bacterial membrane causing leakage of cellular contents. Transient leakage is classified as “graded,” where all vesicles in a population leak partially, or “all-or-none,” where some vesicles leak completely. However, the molecular interactions underlying transient leakage have eluded experimental determination. Here, dye leakage experiments with the AMP piscidin 1 (P1) show that graded leakage can be converted to all-or-none by simply adding a defect-promoting lysophospholipid. Molecular dynamics simulations demonstrate that area stress arising from membrane asymmetry decreases the energy of pore formation and is highly lipid dependent. Furthermore, lipids and peptides translocate the bilayer through these pores, leading to area-relaxed states where poration is highly unfavorable. Even pores too small to leak dye relieve area stress; they are the “none” component of all-or-none release. These observations lead to development of a quantitative model where graded and all-or-none leakage are treated as a continuum explained by a single mechanism that accounts for the local peptide concentration and probabilities of different pore sizes. This unified model accurately reproduces the P1 dye leakage data and provides an explanation for varying pore energy, size, and probability within the framework of asymmetry-driven poration. This model is expected to be applicable to other MAPs, including cell-penetrating peptides, and could provide a framework for designing peptides with greater cellular specificity, a long-sought outcome.